Impact of self-correction on extrovert and introvert students in the EFL writing progress - Hajimohammadi, Reza (2012)
Personalities of individuals have undeniable effects on second language acquisition and learning. Some studies indicate that personality traits have different types of effects on the learners’ second language development (Wang, 2004; Zhang, 2008). In addition, many studies show that corrective feedback in the classroom situation is needed for improving students’ writings (Ferris, 2001). There are not many studies that show effective error correction techniques in writing with regard to different personality traits of the language learners. The treatment of errors in writing has undergone many changes over the last decade. The previous approaches of English as a Second Language (ESL) writing involves teachers mainly underlining students’ errors. The more recent approaches are comparatively task-based where students are responsible for correcting their own errors. The emphasis has also changed from attending to errors that may hinder communication (Byrne, 1988; Power, 2002; Terrell, 1985; Van Houten, 1980). Teachers are expected to provide feedback to learners on the quality of the learners writing so that the necessary corrections can be made. To investigate the impact of self-correction method and to evaluate the impact of personality trai ts of Extroversion/Introversion on the writing progress of the pre-intermediate learners in the morphological, lexical, syntactic, and mechanical categories of errors, the quantitative and qualitative methods with regard to the following null hypotheses that have been proposed: 1. The self-correction method and the teacher-correction method are not significantly different in affecting students’ writing progress. 2. Self-correction does not affect the writing progress of EFL students who are extroverts and introverts. 3. There is no significant difference in the morphological category of errors committed during the writing progress between EFL students who are extroverts and introverts. 4. There is no significant difference in the lexical category of errors committed during the writing progress between EFL students who are extroverts and introverts. 5. There is no significant difference in the syntactic category of errors committed during the writing progress between EFL students who are extroverts and introverts. 6. There is no significant difference in the mechanical category of errors committed during the writing progress between EFL students who are extroverts and introverts. In addition, the research question in the qualitative method is focused on: 1) How do extroverted and introverted EFL students perceive their roles as editors in self-correction groups? One hundred and twenty (120) pre-intermediate Iranian female of English as a Foreign Language (EFL) students were selected for the quantitative method by employing the Nelson English Language Test (NELT) and the Eysenck Personality Questionnaire (EPQ). They were assigned to four different groups:two groups were extroverts and two groups were introverts. Subsequently, they were given five expository topics to write about in a five-week period. When one extroverted and one introverted group used self-correction method, the teacher corrected the writings of the other two extroverted and introverted groups. Besides that, three extrovert and three introvert students were selected for the qualitative method. They were students of different universities in different disciplines of study. The information documented from participant structured indepth interviews. There were 6 sessions of interviews done in 6 weeks. These interview sessions included asking questions, listening to students, and documenting students’ responses. The results obtained showed that personality types had no significant effect on learners' progress in writing. Self-correction method showed to be significant at .05. Consequently, the first null-Hypothesis was rejected in the present study while the second and third null-Hypotheses were supported. According to the results of the Repeated Measure ANOVA, the third, fourth, fifth, and sixth null-Hypotheses were rejected. Finally, the result of students’ perceptions indicated that they believed teacher correction feedback is necessary and the teacher is the most reliable person in giving feedback; without the teacher correction feedback they could not correct and improve their writing.